1997
DOI: 10.1080/00034989760527
|View full text |Cite
|
Sign up to set email alerts
|

The scourge of HIV related tuberculosis: a cohort study in a district general hospital in Malawi

Abstract: Malawi is similar to a number of other African countries in having an escalating, HIV-related, tuberculosis (TB) epidemic. A prospective study was carried out to determine the pattern of disease and HIV serostatus in unselected, adult, TB patients consecutively admitted to a large, district general hospital in Zomba (in the Southern region of Malawi). Clinical details were obtained, from the district TB register, for the 714, adult TB patients, aged > or = 15 years, who were registered with the district TB off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 8 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Although HIV coinfection is well recognized to be associated with higher proportions of smear-negative PTB and EPTB compared to HIV-uninfected cases, 710 this study demonstrated that these patterns are seen across all CD4 strata, even in those with CD4 counts ≥ 500 cells/μL. This may reflect the profound impact that HIV sero-conversion has on host anti-mycobacterial immune responses.…”
Section: Discussionmentioning
confidence: 58%
“…Although HIV coinfection is well recognized to be associated with higher proportions of smear-negative PTB and EPTB compared to HIV-uninfected cases, 710 this study demonstrated that these patterns are seen across all CD4 strata, even in those with CD4 counts ≥ 500 cells/μL. This may reflect the profound impact that HIV sero-conversion has on host anti-mycobacterial immune responses.…”
Section: Discussionmentioning
confidence: 58%